Push versus Pull motivations in entrepreneurial intention: The mediating effect of perceived risk and opportunity recognition - Ricardo Martínez-Ca\~nas; Pablo Ruiz-Palomino; Juan José Jiménez-Moreno; Jorge Linuesa-Langreo (European Research on Management and Business Economics (ERMBE), 2023)
Push and pull driving factors are important motivational antecedents of entrepreneurial intention. Perceptual variables, such as perceived risk in venture creation and opportunity recognition, also play a significant role in this question. However, the existing research has not analyzed all these factors in conjunction, which would enable better identification of entrepreneurial intention. This study advances the understanding of the relationship between push-pull factors and entrepreneurial intention through an analysis of the mediating effects of perceived risk and opportunity recognition. The results of a structural equation model (partial least squares, PLS) applied to a sample of 616 Spanish undergraduate students reveal that the influence of pull factors on entrepreneurial intention is positive, and partially mediated by opportunity recognition. However, the influence of push factors on entrepreneurial intention is indirect and negative. Push factors have a negative impact on entrepreneurial intention, increasing individuals' perceptions of risk in venture creation and undermining their opportunity recognition. The paper extends the current knowledge on how entrepreneurial intention is formed, integrating the Push-Pull Theory into Krueger's 1993 Model of Entrepreneurial Intention, thus incorporating motivational and perceptual variables into a unified model. The results suggest practical implications for forming entrepreneurial intention in individuals from three perspectives: entrepreneurship education, public policy and practitioners. Specifically, these implications mainly focus on the importance of designing programs and policies aimed at favoring pull-related motivations (i.e., self-realization, independence), as well as helping develop perceptions that venture creation entails low risk and that an interesting high-value added business opportunity is recognized.
Keywords: L26; M10; M13; 650; Push-pull factors; Entrepreneurial intention; Perceived risk; Opportunity Recognition